A boundary vorticity diagnosis of the flows in a model pump-turbine in turbine mode. (June 2020) - Lu, Guocheng; Li, Deyou; Zuo, Zhigang; Liu, Shuhong; Wang, Hongjie
Abstract: In the present study, the internal flow field in a model pump-turbine operating in turbine mode was numerically studied. By recognizing that appearance of boundary vorticity flux (BVF)'s peaks might act as the precursors of flow separation in turbomachines, flow diagnosis based on the boundary vorticity dynamics was then performed. It was shown that the effect of the BVF distribution at the condition in design operating zone is to weaken the axial vorticity component ω z, as well as to enhance the radial and circumferential vorticity components ω r and ω θ . Thus, the peaks of the axial BVF component σ z led to the strong weakening of ω z, which is responsible for the flow separations. Geometric optimization for the runner was then achieved by modifying the inlet angle of the blade from 14° to 16°. The optimization successfully suppressed the occurrence of the flow separations and improved the moment on the runner at design operating condition by 4%, which was achieved by the redistribution of the axial BVF component generated by pressure σ p z on the pressure side. The fact that only an accurate steady simulation is required for the analysis indicates the great potential application of this method in engineering practice. Highlights: Boundary vorticity diagnosis was performed in turbine mode of a pump-turbine. The mechanism of the flow separation in the runner passages was firstly explained. The distributions of the BVF's contributions to the moment on the runner were studied. The results of diagnosis were utilized in the optimization on the runner.